Growth analysis of açaí palm trees (Euterpe oleracea Mart.) in floodplain of Amazon estuary - Nogueira, Oscar Lameira; Conceição, Heráclito Eugênio Oliveira da (Pesquisa Agropecuaria Brasileira, 2000)
With the objective of analyzing the palm heart tree growth, in lowland areas submitted to the palm heart exploration, aiming to subsidize the rational handling of the species, a study was accomplished in the county of Igarapé-Miri, PA, Brazil. All of the stems and new budding of three plants of different ages (12, 24, 36 and 48 months after heart extraction) were sampled, and the following components were collected for dry matter evaluation: leaflets, rachis + petioles, sheath + palm hearts and trunks. Representative clumps of the population were selected based on the medium height of the trunks, and number of shoots and leaves. The total dry matter production was 2.68, 5.25, 9.23 and 42.91 kg per plant at 12, 24, 36 and 48 months after the palm heart extraction, respectively. In the recently explored palm heart areas the leaflets represented about 40% of the total weight of the aerial part of the plant and the trunks 10%. After 48 months, in recomposed areas, the trunks were responsible for 73% of the total weight of the plant, while the leaflets only for 10%. Twelve months after the cutting of palm heart, the plants presented medium height of 1 m, and reached more than 3 m after 48 months.